Uncontrolled Blood Pressure and Associated Factors Among Persons With Diabetes: A Community Based Study From Kerala, India - Sreedevi, Aswathy; Krishnapillai, Vijayakumar; Menon, Vishnu B.; Mathew, Minu Maria; Nair, Rajeesh R.; Pillai, Gopal S.; Numpelil, Mathews; Menon, Jaideep; Marwaha, Vishal (Frontiers in Public Health, 2022)
The coexistence of raised blood pressure (BP) in people with type 2 diabetes mellitus (T2DM) is a major contributor to the development and progression of both macrovascular and microvascular complications. The aim of our study was to determine the prevalence of uncontrolled BP and its associated factors in persons with T2DM in a district in Kerala. Methods The study was conducted in Ernakulam district in Kerala, and a total of 3,092 individuals with T2DM were enrolled after obtaining consent. Those with a BP “above or equal to 140 mmHg” and/or “above or equal to 90 mmHg” were thus considered to have uncontrolled BP. If the BP was equal or >140 and/or 90 mmHg, a repeat reading was taken after 30 min and the average of the two was considered. Basic demographic details were enquired along with electronic measurement of BP, HbA1c estimation and screening for diabetic retinopathy, peripheral arterial disease (PAD), and peripheral neuropathy. Quantitative and qualitative variables were expressed as mean (SD) and proportions, respectively. The model for determinants of uncontrolled BP was developed adjusting for age, gender, education, duration of diabetes, occupation, body mass index (BMI) and clustering effect. Results The mean age of the study population was 59.51 ± 9.84 years. The mean duration of T2DM was found to be 11.3 ± 6.64 years. The proportion of uncontrolled HTN adjusted for clustering was 60% (95% CI 58 and 62%). Among them, only one in two persons (53.3%) had a history of hypertension. Age >60 years [adjusted odds ratio (aOR) 1.48, 95% CI 1.24, 1.76; p < 0.001], unemployment (aOR 1.33, 95% CI 1.01, 1.75; p < 0.01), duration of diabetes > 11 years (aOR 1.42, 95% CI 1.19, 1.68; p < 0.001), and BMI ≥23 (aOR 1.33, 95% CI 1.10, 1.59; p < 0.002) were found to be independent determinants of high BP levels when adjusted for the aforementioned variables, gender, education, and cluster effect. The association between complications, such as peripheral neuropathy, PAD, and retinopathy showed a higher risk among those with uncontrolled BP. Retinopathy was 1.35 times more (95% CI 1.02, 1.7, p < 0.03), PAD was 1.6 times more (95% CI 1.2, 2.07, p < 0.001), and peripheral neuropathy was 1.5 (95% CI 1.14, 1.9, p < 0.003) times more compared to their counterparts. Conclusion Target BP levels were far from being achieved in a good majority of the persons with T2DM. To reduce further macrovascular and microvascular events among people with T2DM, effective awareness and more stringent screening measures need to be employed in this population.